Kemampuan Ekstrak Daun Bandotan (Ageratum conyzoides L.) dalam Mempertahankan Kesegaran Buah Tomat(Solanum lycopersicum L. var. Permata) - Mukarlina, Suryati, Riza Linda, (Jurnal Protobiont, 2016)
The tomato (Solanum lycopersicum L.Var. Permata) is one of the horticultural crops that contain vitamin C with potential for health. During the ripening process in storage, the tomato will experiencea more rapid weight loss and decay caused by respiration and bacteria. The storage life of the tomato can be extended by adding edible film from plant extracts that contain secondary hydrocolloid and metabolite compounds. This research aimed to find out the effect of the bandotan (A. conyzoides L.) leaf extract of different concentrations on the freshness of the tomato (S. lycopersicum L.) and to find out the best concentration of the bandotan (A. conyzoides L.) leaf extract to maintain the freshness of tomato (S. lycopersicum L.). The research was carried out from February to April 2015. The experiment used in this research was a completely randomized design. The concentrations of the bandotan extract used consisted of 4 treatments i.e. 0 ppm (P1), 10 ppm (P2), 20 ppm (P3) and 30 ppm (P4). The research findings indicated that the 30 ppm treatment was better at a weight loss parameter of 8.67 and a density of bacteria at 70.5 x 103. The treatments of 10 ppm, 20 ppm and 30 ppm had the ability to maintain the content of vitamin C.